RECONSTRUCTION OF AL-ISLAM AND KEMUHAMMADIYAHAN IN M. AMIN ABDULLAH 'S VIEW - Andhim, Muk; Ali, Mohamad (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
The process of organizing Al-Islam and Kemuhammadiyahan (AIK) in Muhammadiyah colleges still leaves many problems, so that scientific reconstruction efforts are needed to be relevant to the demands of the times. The problem posed is how the reconstruction of scientific al-Islam and kemuhammadiyahan in the view of M. Amin Abdullah, and its implications for the practice of learning AIK in Muhammadiyah colleges. This research is a library research using the hermeneutic-philosophical approach. Whereas in analyzing data using data reduction steps, data display and drawing conclusions. The results of this study indicate that, AIK's scientific reconstruction in the view of M. Amin Abdullah has a pattern of reconstruction. He made the Theoantropocentric monotheistic ethics the basis of ontology, collective scientific epistemology, rationality-collaborative and comprehensive that combines religious texts, philosophy and the development of science-technology. Axiologically, it is oriented to the common good (common good) in the form of universal principles of humanity, justice and freedom. The implication, the aim of AIK is to form strong human beings in the aspects of spirituality (muttaqin), intellect (‘alim), and have a high social concern (muhsin). Teaching material includes cross disciplines and integrated approaches. Andragogy learning approaches and active learning learning methods. Evaluation of learning in the form of non-test in the form of portfolio and assignments.